Isolamento social devido a SARS-COV-2: impacto nas disfunções dos músculos do assoalho pélvico - Brilhante, Magdalena Muryelle Silva (2021)
Objective: To assess the impact of social isolation due to SARS-CoV-2 on the prevalence and severity of urinary incontinence and the sexual function of nulliparous women. Methods: Observational, longitudinal study, carried out from August / 2019 to September / 2020, at the Faculty of Health Sciences of Trairi / RN, with 37 nulliparous women from 18 to 35 years old, who answered the socio-anthropometric evaluation, to the Incontinence Severity Index Questionaire (ISI-Q), King's Health Questionnaire (KHQ), Female Sexual Function Index (FSFI), Short Form Health Survey 36 (SF-36), and the Stunkard, Sorensen and Schlusinger Silhouette Scale, before and during isolation due to SARS-CoV-2. For the statistical analysis, the Wilcoxon Test was applied, and the Spearman Correlation Coefficient, due to the non-parametric distribution. Significance level p≤0.05. Results: During social isolation, there was an improvement in urge incontinence (p = 0.01) and in the frequency of urinary incontinence (p = 0.03). The severity of urinary incontinence had a positive correlation with: general health perception (p = 0.02; r = 0.65); physical (p = 0.03; r = 0.60) and social (p = 0.001; r = 0.82) and social limitations. The number of physically active women decreased by 21.62%, there was an improvement in the orgasm domain of the FSFI (p = 0.0081) and worsening in the pain domain of the SF36 (<0.0001) during social isolation, in addition , the SF-36 General State of Health domain showed a weak positive correlation with sexual function (p = 0.04; r = 0.37) during social isolation. Conclusion: The social isolation of SARS-CoV-2 improved urge incontinence and frequency of urinary incontinence. The more severe the urinary incontinence, the worse the general perception of health, physical and social limitations during isolation. It also favored the improvement of orgasmic function, worsened the pain assessed by the SF-36, and contributed to a weak positive correlation between sexual function and quality of life.